Techniques for Studying Materials, Microstructural Examination - Yeoh Catriona; Barber Zoe; DoITPoMS, University of Cambridge
Este grupo de animaciones comprende diversos diagramas de fase interactivos: Fe-C, hierro de fundicin̤ gris, hierro de fundicin̤ blanco, latn̤ alfa y latn̤ alfa-beta. Incluye los siguientes elementos:Phase diagram for the Fe-C systemGrey cast iron with micrographSpheroidal cast iron with micrographWhite cast iron with micrographα-brass (70 wt% Cu, 30 wt% Zn) with micrographPeritectic (21 wt%t Cu, 79 wt% Sn) with micrographα β-brass (60 wt% Cu, 40 wt% Zn) with micrograph